Educación administrativa y financiera en educación básica secundaria: una revisión sistemática de literatura 2016–2023 (Revista "Boletín el Conuco", 2023)
This study explores the role of administrative and financial education in secondary education, focusing on how it fosters entrepreneurship and innovation from an early stage. Business adminis- tration is fundamental to creating new businesses and strengthening the economy skills that can be cultivated during school, guiding students to begin technical studies. Many young people are unaware of the options for technical and professional training available after completing the ninth grade. The research uses a systematic literature review to analyze theoretical contributions on administrative education in secondary school. The initial search in databases (Dialnet, Redalyc, Scielo) produced 78 documents, of which 39 were identified for significant contributions in ti- tles and abstracts, and 17 fully met the inclusion and exclusion criteria defined under the PRISMA methodology. The review results highlight two main points: first, the importance of identifying and examining documents that address adminis- trative and financial education among young people, considering technical education in secondary school. Second, it emphasizes the value of introducing financial and savings concepts at a young age, equipping students with foundational knowl- edge in economics and work, which is essential for their future financial development.
Keywords: Financial Education; secundary education; entrepreneurship; technical training; literature review